Deep cutting injury from the edges of a snowboard. Issue 1 (29th January 2004) - Matsunaga, T; Saitoh, S; Tanikawa, H; Hayashi, M; Ohira, M; Kimura, T
Abstract : A laceration deep enough to reach the bone occurs very rarely in skiing or snowboarding. Two such cases are presented here. In one case, the popliteal fossa of a skier was cut during a collision with a snowboarder. All structures posterior to the knee were severed and the leg became ischaemic. The other case was of a snowboarder who sustained a deep cut to the distal forearm during landing after a jump, resulting in a "spaghetti wrist".